Completeness of Medical Record Files and The Timeliness of BPJS Claims on Inpatients With Bronchitis Cases at Purwokerto Islamic Hospital - Regina, Putri Sepna; Fauzi, Harry (Procedia of Engineering and Life Science, 2024)
One of the things that determines the quality of medical services provided by hospitals is the availability of adequate and complete data or information regarding medical records so that it will affect the submission of BPJS claims. This study was conducted to describe the completeness of medical record files and the timeliness of BPJS claims on inpatients with bronchitis cases at Purwokerto Islamic Hospital. This study uses quantitative methods with descriptive research design, data collection design using cross sectional. Completeness of medical record file on inpatients with bronchitis cases with indicators of participant eligibility letter, spporting examination, code accuracy, and resume of inpatient bills or billing costs with a complete category of 75 (100%), medical resumes with a complete category of 34 (45,33%) and an incomplete category of 41 (54,67%), and indicators of hospitalization orders with a complete category of 6 (8%) and an incomplete category of 69 (92%). The timeliness of inpatient BPJS claims with the timely category was 49 (65,33%) and the untimely category was 26 (34,67%).